Pengaruh Terapi Pijat Bayi Terhadap Frekuensi Menyusu Neonatus Yang Dirawat Di Ruang Perinatologi - Desak Gede Yenny Apriani; DESAK MADE FIRSIA SASTRA PUTRI (JURNAL MEDIKA USADA, 2019)
THE EFFECT OF INFANT MASSAGE THERAPY ON THE FREQUENCY OF BREASTFEEDING OF NEONATES TREATED IN THE PERINATOLOGY ROOM Desak Gede Yenny Apriani 1, Desak Made Firsia Sastra Putri2 2TIKES Advaita Medika Tabanan, Korespondensi: yennyapriani2004@gmail.com ABSTRACT Background: According to the results of the 2010 Riskesdas, 78.5% of neonatal deaths were caused by respiratory problems, prematurity, sepsis and hypothermia. In addition, the problem that occurs in neonates is the low frequency of breastfeeding. Baby massage is an effort to deal with the problem of lazy drinking in the neonateThe purpose: To determine the effect of infant massage therapy on the frequency of breastfeeding of neonates treated in the Perinatology Room of BRSUD in Tabanan Regency. Method: The design of this study is quasy-experiment with the One-Group Pre-test-posttest Design approach. The sampling technique used is nonprobability sampling, namely purposive sampling, obtained a sample of 30 respondents. Data collection is done by making observations before baby massage therapy is carried out (pre-test) then give treatment (intervention) and make observations again after the baby massage therapy is done (post-test). The statistical test used was the Wilcoxon Signed Rank Test with p <0.05.Results: In this study, the average frequency of neonatal breastfeeding before infant massage therapy was 6.40 with a standard deviation of 1.673. The average frequency of neonatal breastfeeding after infant massage therapy has increased by 11.13 with a standard deviation of 2.240. The Wilcoxon Signed rank test statistical test results in a significance (p) of 0,000, where the value is (p <0.05) then Ha is accepted.Conclusion: There is an effect of infant massage therapy on the frequency of neonatal breastfeeding. Keywords: Frequency of Breastfeeding, Infant Massage, Neonates, Perinatology.